15x-17=-4+2x-13

Simple and best practice solution for 15x-17=-4+2x-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15x-17=-4+2x-13 equation:



15x-17=-4+2x-13
We move all terms to the left:
15x-17-(-4+2x-13)=0
We add all the numbers together, and all the variables
15x-(2x-17)-17=0
We get rid of parentheses
15x-2x+17-17=0
We add all the numbers together, and all the variables
13x=0
x=0/13
x=0

See similar equations:

| x+3/7=8 | | −2x−x+8=0 | | 5-6=-3/k | | |5p+7|=27 | | 7/9x=-3/18 | | 7x+31=180 | | 1+11a=6-3a | | 0.7m-2.2=2.5+1.2m | | 3x-4=-1x+4 | | 22x=1900x+3 | | 3/4-1/2x=4 | | -4+x/6=6 | | -3x-4=x+3 | | |7+5p|=27 | | |w|+5=11 | | (x/(180=2x))=1 | | -9/2=5/4m+m | | x/(180=2x)=1 | | x+2/x-6+9/x+5=17 | | 3x-2=2x+59 | | 2x+8-5x+3=-13+8x-5 | | 3x+1=2(3x12) | | 4/5(10+15d)=8d-15 | | 5x+12=3x-110 | | 20=-4f+24+14 | | 4(x+6)-13=43+2x+12 | | -3x+4x+1=-(-x-1) | | 7x-(9x2)=5x(-6) | | 5x+41=(-2x)+48 | | -4f+24+14=20 | | 4r=-12+8r | | 3/5y=-40 |

Equations solver categories